Sustainability of Local Literacy towards Epidemic Virus COVID-19 in Indonesia: Hermeneutic Theory - Paisal Manurung (Lingua Cultura, 2022)
The research aimed to investigate all elements of local literary resilience in Indonesia using hermeneutic theoryinterpretation of issues, giving an understanding of issues, and translating its issues. The interesting thing about the research was local literacy as the creation of harmony in society had shifted from the cultural foundation. Local literacy in society was a transformation of the harmony of lives, ethics, attitudes, and ordinances in fulfilling spiritual and bodily elements. It certainly prioritized all elements in society and government to sustain the local literacy in Indonesia towards of epidemic virus COVID-19. The research applied a qualitative approach. Primary data sources were national and international scientific journals and used authentic phenomenological issues. Based on data collected and indicated the presentation of theory, it is found that there are sustainabilities of local literacy on epidemic virus COVID-19. They are the most crucial the findings reveal local literacy to sustain the resilience of local literacy: resilience to the noble values of the culture, the cooperation of the community with government, resilience to maintain the balance of nature and man, and the resilience of community groups with the other community.